Importance of the double knee bend phase Importance of using weightlifting movements in sports training - Gattone, A.; Schilling, B.; Pierce, K.; Byrd, R. (coachesinfo.com)
Importance of the Double Knee Bend Phase: The vertical ground reaction forces commonly observed during a pulling movement can be noted in Figure 15. As previously discussed most lifters of reasonable standard use a stretch shortening cycle called the "double knee bend" phase. This consists of an un-weighting period in conjunction with eccentric and concentric muscle actions. This double knee bend phase is important because: 1) it reduces the tension on the back (Enoka 1979) and the sudden forceful stretch in some manner enhances the concentric portion of the pull. The exact mechanism whereby a stretch reflex enhances concentric action is not fully understood, but may involve: increased elastic energy use, a myototic or stretch reflex, optimising muscle length, imparting additional energy into the contractile apparatus or optimising muscle activation patterns (Enoka 1979, Bobbert et al. 1996, Newton et al.1997).